COMPETITIVE MODEL PROPOSAL FOR THE AZERBAIJAN WINE INDUSTRY: TALENT-BASED ORGANIZATIONAL MODEL - BASHIROV, Intiqam (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The main aim of this study is to develop a talent-based model proposition in line with the resource-based approach by assessing the strategic position of Azerbaijan's wine industry, which is globally recognized as an important wine producing country.It is noted that in the context of very important changes and events taking place in the world today, the phenomenon of competition expresses competition in all spheres of life and day by day increases its intensity and challenges modern business.The article widely uses methods of comparative analysis of the experience of foreign countries, analysis of statistical dynamics, and in-depth analyzes of economic growth in a competitive environment.The author notes that in order for businesses to compete and, moreover, achieve sustainable competitive advantage, they need to understand that the basis of competition has changed, and accordingly everyone must reconsider their approaches and define a new road map for themselves as strategic support with new methods in management. This new understanding of strategy allows companies to be unique, inimitable and responsive to define their strategy and prepare action plans to meet changing customer needs, create customer value and provide quality and low-cost products and services.The author emphasizes that businesses now realize that it is impossible to compete and survive using old methods. It is noted that the resource-based view is used as a new approach, which involves the harmonization of resources and business capabilities with their external environment to produce unique products and services.Azerbaijani wine industry businesses that can redefine their boundaries and develop external relationships using a talent-based model can expand their reach and influence to new groups of employees and entrepreneurs. In this way, Azerbaijani wine industry enterprises can create great new opportunities and offer these groups opportunities to participate in the global economy. This perspective, which sheds light on the dominant organizational logic of powerful players who influence or share the behavior of others, includes foreign competitors, suppliers and employees in the global economy. In this regard, it is very important for the Azerbaijani wine industry to have a good understanding of the interaction between global and local dynamics.
Keywords: resource-based approach; competitiveness; strategy; talent-based organizational model; Azerbaijani wine industry